Causal factors of e-commerce success affecting the retail performance in online sales business - Kongchoochuy, Eakkaphon; U-on, Vichit (Edelweiss Applied Science and Technology, 2025)
The online sales business has significant potential for expansion, driving innovation and economic growth through e-commerce. However, challenges persist in online sales, such as a lack of market analysis, disorganized product delivery, failure to update product listings in real time, insufficient after-sales service, and price undercutting by competitors. These issues can negatively impact customer satisfaction, brand reputation, and overall retail performance. The objectives of this research study were: 1) to study the causal factors affecting e-commerce success and retail performance in the online sales business, 2) to study the influence of causal factors of e-commerce success affecting retail performance in the online sales business, and 3) to develop a model of the causal factors of e-commerce success affecting retail performance in the online sales business. A researcher collected data from interviews and online questionnaires with the cosmetic business, from July 2024 to September 2024, by collecting a sample of 560 people. The results of the analysis concluded that social media integration affected e-commerce success, social media integration affected retail performance through e-commerce success, distribution management affected e-commerce success, distribution management affected retail performance through e-commerce success, content marketing affected e-commerce success, content marketing affected retail performance through e-commerce success, and e-commerce success affected retail performance. The online sales business can develop a plan in areas such as social media integration, distribution management, and content marketing to ensure that the business can identify the success of e-commerce and retail performance. Additionally, it enables the business to meet its own needs and carry out the decision-making process for making purchases effectively.